Verificação automática de projetos em BIM: um estudo do código de obras e posturas de Crateús, CE - Siqueira, Stelamaris Alves de (2022)
Using Building Information Modeling (BIM) has been a means of improving several processes, including project approval. With BIM models, it is possible to automatically verify the compliance of projects with building codes, standards, laws or even criteria established by building designers. However, this is not a simple process and requires this set of criteria to be translated into a programming language, being the clarity of the current law a fundamental requirement for its aplication. In small towns, such as Crateús, this possibility can bring benefits to construction entrepreneurs and public authorities, which led to the following question: how can visual programming language for automatic checking of BIM projects be applied to Building Code of Crateús? Thus, the present work aimed to analyze the applicability of Visual Programming Language (VPL) for automatic checking of BIM projects, according to the Building Code of Crateús. Following the footsteps of Design Science Research, a literature review was carried out, which supported the elaboration of interview scripts, applied to four agents, including the city hall analyst. It was possible to map the approval process and the technical evaluation of projects, having been observed as the main difficulty the proper application of the law, which reinforces the potential of applying an automatic check. Thus, it was verified which Building Code's residential projects approval criteria could be automatically checked through BIM models, to then implement the proposed artifact, consisting of Visual Programming Language routines using Dynamo, associated with Revit, a modelling software. With the code developed, its applicability was verified, through its application in a project recently approved by the city hall, granted by one of the interviewees. It was noticed automatic checks were assertive with manual results, which demonstrated its functionality. Thus, it was possible to conclude the applicability of visual programming language for automatic checking of BIM projects according to Crateús' Building Code. Still, it is possible to observe opportunities to improve the law in question, which contributes to the updating of municipal laws, as pointed out in the results of this work. Future studies were also proposed.